Eight-Port millimeter wave MIMO antenna loaded with novel frequency selective surface for higher data rate transmission - Malini Soman; Manish Sharma; Seema Narwal; Tanweer Ali (PLoS ONE, 2026)
In this research, an eight-port multiple-input-multiple-output (MIMO) antenna integrated with frequency frequency-selective surface (FSS) is presented for 28.0 GHz millimeter-wave (n257/n261) bands. The radiating patch consists of a circular-ring shape with a plus-shaped stub embedded in it. The antenna element is fed by a 50 Ω microstrip feed line and a quarter-wave transformer as a matching network. The MIMO antenna measures 50 mm × 50 mm and achieves spatial diversity through an orthogonal arrangement of eight radiating elements. A 10 × 10 array of FSS is also designed at 28.0 GHz and measures 60 mm × 60 mm. The FSS structure is intended for a band-stop filter and consists of a circular ring with a plus-shaped stub. The proposed MIMO antenna has a peak realized gain of 13.89 dBi and features directional 2-D radiation patterns. The specific absorption rate analysis is also performed, resulting in a value of 0.0274 W/kg at 28.0 GHz.